Engineering properties and microstructural characteristics of cement and geopolymer based mortars using nontraditional supplementary cementitious materials / Sumesh Mathialagan - Sumesh , Mathialagan (2020)
The concrete repair and rehabilitation industry grows rapidly due to deterioration, damage and defects in concrete structures. For various reasons, the concrete construction industry is not sustainable; because it consumes huge quantities of virgin materials, the usage of Portland cement as prime binder. The production of cement is a major contributor to greenhouse gas emissions. In addition, the high cost of commercial repair material. Therefore, it is necessary to develop cost-effective alternative repair materials for concrete repairs. There have been many standard repair materials available in the market, which are costly and not affordable to common people. However, research works on the use of alternative, non-traditional pozzolanic materials in repair and rehabilitation is gaining momentum. Industrial wastes and by-products such as palm oil fuel ash (POFA), palm oil clinker (POC), ground granulated blast furnace slag (GGBS), bottom ash (BA), and fly ash (FA) have shown promising results as pozzolanic materials. As the world’s second-largest palm oil producer, Malaysia has abundant industrial by-products of POFA and POC. The by-products of palm oil industries are signified as non-traditional supplementary cementitious materials, which have not been addressed in the previous research works as repair mortars. The present study focused on cement and geopolymer-based mortars with partial replacement of POFA, treated palm oil fuel ash (TPOFA), POCP and BA. GGBS and FA were utilized as source material for geopolymer mortars. The significant parameters were investigated on association with the better understanding of the interfacial transition zone, microstructures, setting behavior, mechanical properties, bond strength and durability in accordance with ASTM standard. Ordinary Portland cement (OPC) was partially replaced by POFA, TPOFA, POCP and BA at 0%, 10%, 20% and 30% by weight. For geopolymer mortars, GGBS was replaced with 20%, 30% and 40% of POFA, TPOFA, POCP and BA by weight. The chemical composition and morphology of binders were examined by X-ray florescence (XRF) and scanning electron microscope (SEM) techniques, respectively. Microstructure of mortar was investigated using SEM, X-ray Diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR) and Thermogravimetric analysis (TGA). Among all the non-traditional SCMs, TPOFA achieved a satisfactory performance in all the investigation conducted. The mortars with TPOFA as the replacement of cement for 10%, 20% and 30% produced higher compressive strengths of 101.8, 88.4 and 83.6 MPa, respectively at 90-day. In case of geopolymer mortar, 30% replacement of GGBS with TPOFA attained the highest 28- day compressive strength of 82.45 MPa. Formation of CH and C-S-H was confirmed by XRD, FTIR and TGA in cement-based mortars. The formation of C–A–S–H gel was identified in GGBS based geopolymer mortars. Moreover, the strength activity index assessment found that pozzolanic activity of TPOFA and BA is better than POCP and POFA based mortar specimen. It is recommended that 10% of pozzolanic cementitious material of POFA, TPOFA, POCP and BA could be used to replace OPC and for geopolymer-based mortars, 30% of pozzolanic cementitious material can be used to replace GGBS in the development of geopolymer mortars in order to develop high strength mortar in the range of 60-100 MPa.